MENEMUKAN MAKNA DALAM KETIDAKPASTIAN - Armin Nasution (UIN Sumatera Utara, 2019)
In order for us to be more calm, I am convinced that we must use all our abilities to continue the future figure. That's what I'm trying to do. I want to show that however there is a meaning in all things that seem meaningless, which surrounds us. You see, the picture might seem chaotic, but